Buchnera has changed flatmate but the repeated replacement of co‐obligate symbionts is not associated with the ecological expansions of their aphid hosts. Issue 8 (19th December 2016) - Meseguer, A. S.; Manzano‐Marín, A.; Coeur d'Acier, A.; Clamens, A.‐L.; Godefroid, M.; Jousselin, E.
Abstract: Symbiotic associations with bacteria have facilitated important evolutionary transitions in insects and resulted in long‐term obligate interactions. Recent evidence suggests that these associations are not always evolutionarily stable and that symbiont replacement, and/or supplementation of an obligate symbiosis by an additional bacterium, has occurred during the history of many insect groups. Yet, the factors favouring one symbiont over another in this evolutionary dynamic are not well understood; progress has been hindered by our incomplete understanding of the distribution of symbionts across phylogenetic and ecological contexts. While many aphids are engaged into an obligate symbiosis with a single Gammaproteobacterium, Buchnera aphidicola, in species of the Lachninae subfamily, this relationship has evolved into a 'ménage à trois', in which Buchnera is complemented by a cosymbiont, usually Serratia symbiotica . Using deep sequencing of 16S rRNA bacterial genes from 128 species of Cinara (the most diverse Lachninae genus), we reveal a highly dynamic dual symbiotic system in this aphid lineage. Most species host both Serratia and Buchnera but, in several clades, endosymbionts related to Sodalis, Erwinia or an unnamed member of the Enterobacteriaceae have replaced Serratia . Endosymbiont genome sequences from four aphid species confirm that these coresident symbionts fulfil essential metabolic functions not ensured by Buchnera . We further demonstrate through comparative phylogenetic analyses that cosymbiont replacement is not associated with the adaptation of aphids to new ecological conditions. We propose that symbiont succession was driven by factors intrinsic to the phenomenon of endosymbiosis, such as rapid genome deterioration or competitive interactions between bacteria with similar metabolic capabilities. Abstract : see also the Perspective by Russell et al